ทัศนคติต่อการปนภาษาอาหรับในหนังสือคำสอนศาสนาอิสลามภาษาไทย - ดาราฉาย ซัลมาณ (วารสารเกษมบัณฑิต, 2016)
บทคัดย่อ การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อศึกษาความคิดเห็นเกี่ยวกับภาษาอาหรับโดยทั่วไป ความคิดเห็นเกี่ยวกับการใช้ภาษาอาหรับปนภาษาไทย และความคิดเห็นเกี่ยวกับบุคลิกภาพและสถานภาพของมุสลิมที่ใช้ภาษาอาหรับปนภาษาไทย ข้อมูลที่ใช้ในการวิเคราะห์เป็นข้อมูลความคิดเห็นของชาวไทยมุสลิมผู้ตอบแบบสอบถามที่มีต่อการปนภาษาอาหรับในหนังสือคำสอนศาสนาอิสลามภาษาไทย สถิติที่ใช้ในการวิเคราะห์ข้อมูลคืออัตราส่วนร้อยละและค่าเฉลี่ย ผลการศึกษาพบว่ากลุ่มตัวอย่างผู้ตอบแบบสอบถามโดยรวมมีความเห็นว่า ภาษาอาหรับเป็นภาษาสำคัญของโลกและเป็นเอกลักษณ์ของมุสลิมทั่วโลก มุสลิมจำเป็นต้องเรียนภาษาอาหรับ กลุ่มตัวอย่างรู้สึกภูมิใจที่ได้เรียนภาษาอาหรับและต้องการเรียนภาษาอาหรับเพิ่มเติม กลุ่มตัวอย่างระบุด้วยว่า การเขียนคำทับศัพท์ภาษาอาหรับด้วยอักษรไทยในหนังสือคำสอนศาสนาอิสลามควรใช้หลักเกณฑ์ตามราชบัณฑิตยสถานเพื่อให้มีมาตรฐานเดียวกัน ควรใช้ถ้อยคำภาษาอาหรับเท่าที่จำเป็น และควรเขียนคำแปลภาษาไทยควบคู่กับถ้อยคำภาษาอาหรับ นอกจากนี้ กลุ่มตัวอย่างแสดงความเห็นว่า มุสลิมที่ใช้ภาษาอาหรับปนภาษาไทยเป็นบุคคลที่มีการศึกษา มีความเชื่อมั่นในตนเอง และมีความน่าเชื่อถือ Abstract The main purposes of this research were: To explore the respondents’ attitudes towards Arabic language in general; To determine the respondents’ attitudes towards Arabic-Thai code mixing styles, and; To investigate the respondents’ attitudes towards personality and social status of Muslims using Arabic-Thai code mixing. The data in this study were obtained from a sample of 360 Thai – Muslims purposively selected form 12 Mosques in Bangkok. The statistical analysis was done in form of percentages and averages. Regarding the result of the study, the majority of respondents agreed that Arabic was an important language representing Muslim identity. Therefore, it was an obligation for Muslims to learn Arabic. The respondents admitted that they were proud to study Arabic and they would like to learn more about it. They also suggested that the use of Arabic loan words in Thai language should strictly follow the standard format set by the Royal Institute of Thailand. In addition, they suggested that Arabic words would be used only where necessary and with translation in Thai. Besides, they agreed on the various personalities and social status of the Muslims using Arabic-Thai code mixing, e.g. high education, self confidence and reliability.